Analisis Jenis-Jenis Frasa pada Kumpulan Teks Eksplanasi dalam Website Liputan6 Edisi Juni 2023 sebagai Sumber Bacaan Siswa SMA - Muhammad Ziddan Rizqon Nafi; Haafizhoh Salzabil Sausan; Hanum Putri Maharani; Tiara Kristya Alfika; Intan Ayu Rahma Yuniar; Asep Purwo Yudi Utomo; Rio Anugrah Rizkiansyah; Erwan Kustriono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Explanatory text is commonly used in Indonesian language learning, especially at the high school level, as it helps students understand the process or cause-and-effect of a phenomenon. In explanatory texts, the structure of sentences and the correct use of phrases are crucial for conveying information clearly and effectively. Understanding the types of phrases in explanatory texts will help students improve their reading skills and text composition. Therefore, it is important to analyze the types of phrases in explanatory texts to improve the quality of reading materials used in learning. This study aims to analyze the types of phrases found in a collection of explanatory texts published on the Liputan6 website in June 2023 as reading material for high school students. The research method used is qualitative descriptive, with data collection techniques involving documentation of explanatory texts available on the website. The analysis results show that nominal, verbal, and adjectival phrases are the dominant types of phrases. Authors commonly use nominal phrases to explain the subject in explanatory texts. In contrast, verbal phrases indicate actions or processes, and adjectival phrases describe the characteristics or states of the objects explained. In conclusion, understanding the types of phrases in explanatory texts is essential for improving students' ability to comprehend, analyze, and construct explanatory texts effectively and systematically.